CONSIDERATIONS OF I’TIBAR AL-MA’ALAT REGARDING REGULATIONS ON ABORTION IN CASES OF RAPE IN INDONESIA - Andi Muh. Taqiyuddin BN; Mustaufiq; Arief, Ahmad; Sarib, Suprijati; Taufik, Bambang (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2025)
This study examines the consideration of I’tibar al-Ma’alat in regulating abortion in cases of rape as stipulated in Articles 116 and 118 of Government Regulation (GR) No. 28 of 2024. This research employs a qualitative approach using a literature review method. The findings indicate that abortion is generally prohibited, except in cases of medical emergency or pregnancy resulting from rape or sexual violence. However, the regulation has not fully reflected the principles of I’tibar al-Ma’alat, particularly in the procedure for proving pregnancy resulting from rape. The requirement of a medical certificate and an investigator’s statement lacks clear standards and does not involve comprehensive medical recommendations from psychiatric and obstetric specialists. This condition potentially undermines legal certainty and the objective of mitigating harm, especially psychological risks faced by rape victims. Therefore, strengthening medical and legal coordination is necessary to ensure the regulation aligns with the consideration of legal implications (ma’al).